Application of a Customer Based Data Monitoring Facility Online Accounting Software For Effectiveness Leadership at Higher Education - Azizah, Nur; Suryana, Endang; Haris, Haris (APTISI Transactions on Management (ATM), 2017)
In a company, the accounting system is very important to manage the financial development, because it contains financial information that can be used to make a decision. Currently already developed Online Accounting Software, where the accounting system can be used anytime and anywhere with an internet connection without having to difficult to handle bookkeeping reports. An accountant is someone who has an important role in the success of financial processing company. Where, to facilitate the process of information media, accountants must be able to convey information both customers who work with the company in order to facilitate leadership in monitoring the company effectively and efficiently without having to come to the company. with Online Accounting Software will minimize criminality because it has been certified ISO / IEC 2700. And for the report has been stored on Cloud to facilitate the leadership of the company in monitoring financial reports in real-time. With the monitoring of customer data, the leader can view, add, delete, or change customer data to the company, so it can facilitate in managing and conveying the customer information that the company has.